ELECTRONIC TAXATION AND TAX YIELD A PRE AND POST COMPARATIVE ANALYSIS - Ihenyen Confidence Joel; Owonaro Dorcas Diweri; Agagowei Rebecca Suotan (ZILLZELL MEDIA PRIMA, 2023)
This scholarly inquiry delves into the intricate interplay among digital taxation and the consequential tax yield. The primary aim of this article is to discern the diverse methodologies by which digital tax systems can be safeguarded and maintained in Nigeria, while also exploring strategies to prevent and mitigate instances of cyber tax crimes. This endeavor is informed by the invaluable insights and lessons garnered from the experiences of other nations in their resolute battle against digital tax fraud. The concept of tax-equivalent yield pertains to the calculation of the rate of return that a taxable bond must attain in order to be on par with the yield generated by a corresponding tax-exempt municipal bond. The process of calculation serves as a valuable instrument for investors to discern and evaluate the disparities in returns between a tax-exempt investment and its taxable counterpart. A cross-sectional research design was used with a sample size determined by statistical power analysis. Secondary data was obtained from the National Bureau of Statistics and analyzed utilizing appropriate statistical techniques, including regression analysis. The model specification indicates that electronic taxation revenue has a favorable but not substantial outcome on economic expansion, while government spending has an unfavorable but insignificant impact on economic growth. The R2 of .852 suggests that the model elucidates 85.2% of the variance in GDP growth, which is a relatively high amount of variance explained. The study concludes that electronic taxation and government spending may have some impact on economic growth, but the effect is not statistically significant. The paper recommends conducting more research to identify other factors that may have a substantial influence on economic growth, improving electronic tax collection methods, and improving the effectiveness and efficiency of government spending. Policymakers should consider both statistical significance and practical significance when making decisions based on empirical research.